ANALISIS KEMAMPUAN BERPIKIR ALJABAR SISWA KELAS IX A SMP NEGERI 12 KOTA SUNGAI PENUH PADA MATERI SPLDV - Afrima Sari, Nada; Yanty Putri Nasution, Eline (Jurnal Riset Pembelajaran Matematika, 2023)
Mathematics plays an important role in helping students solve problems in everyday life. The National Council Of Teacher Of Mathematics (NCTM) (in Saputro & Mampouw, 2018) argues that algebra is a sub-field of mathematics that utilizes mathematical theories to describe the relationship between objects. Therefore, the use of algebra in teaching mathematics can improve students' mathematical thinking skills, known as algebraic thinking skills. The research method used in this research is qualitative. According to Wijaya (2018) qualitative research is a form of research based on a post-positivist philosophy that emphasizes inductive reasoning and utilizes descriptive data as a basis for drawing conclusions about the deeper implications of a series of generalizations. Based on the results of data analysis and discussion of research regarding the algebraic thinking skills of students of SMP Negeri 12 Kota Sungai Penuh class IX A in solving SPLDV material questions, it can be concluded that the algebraic thinking skills of students IX A are divided into three categories, namely there are 13.63% of students with ability level high level, 27.28% of students with medium level ability and 59.09% of students with low level algebra ability.